Implementasi Akad Pembiayaan Murabahah Pada Koperasi Pojok Syariah - Derani Hotimah; Dandan Irawan; Nanang Sobarna (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2022)
Murabahah Financing Agreement is one of the transactions of buying and selling an item or asset that is affirmed at the acquisition price to the buyer and the buyer will pay it at an additional price as a profit. One of the foundations used to manage the financing of this murabahah is the Fatwa DSN-MUI No.04/DSN-MUI/ IV/2000 concerning Murabahah. This study aims to determine the suitability between the implementation of the murabahah financing agreement at Koperasi Pojok Syariah in the perspective of DSN-MUI Fatwa No.04/DSN-MUI/IV/2000 concerning Murabahah. The research method used is a descriptive analysis and quantitative approach through observation, interviews with informants and the distribution of questionnaires to get an overview of the implementation of the murabahah financing agreement. The results of this study, the implementation of the murabahah financing agreement at Koperasi Pojok Syariah is in accordance with the provisions of the DSN-MUI Fatwa No.04 / DSN-MUI / IV / 2000 concerning Murabahah,